Déjouer les dominations et les contraintes en ligne : un état des connaissances - Françoise DAUCÉ; Ksenia ERMOSHINA; Bella OSTROMOOUKHOVA (Tic & Société)
The beginnings of Web 2.0 in the 2000s fostered a political utopia correlating democratic participation, libertarian ideals and horizontality, which facilitated the dissemination and integration of new technologies into our society. However, disillusionment and concern subsequently prevailed in the face of new forms of political and economic domination and oppression based on digital functionalities. This article first examines the democratic hopes placed on digital participation and then looks at forms of domination that rely on the internet as a tool of control. Following this description of constraints, we analyse the multiple ways in which they may be challenged. Web professionals, digital freedom activists, hackers and ordinary users create alternative knowledge or devise solutions to get round these constraints, typically on small scales with actions that are rooted in the materiality of the network. We conclude by arguing that the digital perspective needs to be decentralized in order to take into account the numerous local experiences that are fueling so many specific and unique ways of bypassing these constraints.